Waginizm jako źródło niezdolności do podjęcia istotnych obowiązków małżeńskich w świetle kan. 1095 n. 3 KPK z 1983 r. - Wybult, Witold (Ius Matrimoniale, 2017)
Vaginismus, understood as a disease / disorder can become a cause of incapacity within the meaning of can. 1095 n. 3 KPK. Incapacitas is an inability to communicate and realize the subject matter of conjugal consent. In this situation a person who has sufficient reasoning ability and is able to discern judgment on important marital obligations is unable in the event of a mental disorder to take up and fulfill important marital obligations. Similarly to impediment impotence which must be characterized by certain qualities. Incapacitas assendii should have the following characteristics: gravity, prioriteness, absoluteness and permanence. In addition, this inability has the clause ob causas naturae psychicae which excludes all forms of physical disability. For this reason, limited vaginismus can never become the cause of the invalidity of marriage within the meaning of can. 1095 n. 3 KPK. Such a cause may be psychogenic vaginismus, which may <hinder> or <prevent> sexual intercourse. In practical considerations a detailed diagnosis of an expert is required to determine the degree of the disease and to determine whether the identified vaginismus is primary, secondary, higher or lower. The separate problem discussed in this article is dyspareunia and vulvodynia. Because of the poor literature it is difficult to say with certainty whether they are the cause of an obstacle or an inability. ental nature.